Pengaruh Pembelajaran Berbasis Proyek Berbantuan Media Komik Terhadap Keterampilan Proses Sains Kimia Materi Laju Reaksi pada Siswa Kelas XI MIPA SMAN 1 Lembar - Irawan, Rizka Sofia; Haris, Mukhtar; Hidayanti, Ermia (Chemistry Education Practice, 2024)
This study aims to examine the impact of project-based learning supported by comic media on students' chemical science process skills in the experimental class XI MIPA at SMAN 1 Lembar, focusing on reaction rate material. The measured science process skills include observing, hypothesizing, planning experiments, using tools and materials, classifying, and communicating. Project-based learning is a method that emphasizes problem-centred instruction, problem-solving, decision-making, and collaborative opportunities for students. This quasi-experimental research employed a pretest-posttest control group design. From a population of 130 students, 62 samples were selected using a one-stage cluster sampling technique and divided into an experimental group (XI MIPA 1) and a control group (XI MIPA 2). Data analysis using N-Gain calculations revealed that the experimental class experienced a medium-level improvement (0.335), significantly higher than the control class's low-level improvement (0.011). Furthermore, the statistical analysis showed that tcount (3.15) exceeded ttable (1.671) at a 5% significance level, indicating that the use of project-based learning supported by comic media had a significant influence. The study concluded that while there was no significant difference between the pretest and posttest results of the two classes, project-based learning with comic media significantly enhanced the chemical science process skills of students in the experimental class compared to those in the control class, particularly for reaction rate material.